Mechanical stress evaluation by neutrons and synchrotron radiation VII : selected, peer reviewed papers from the 7th International Conference on Mechanical Stress Evaluation by Neutrons and Synchrotron Radiation (MECA SENS VII 2013), September 10-12, 2013, Sydney, Australia - Holden, Thomas M.; Muránsky, Ondrej; Hamelin, Cory J. (Materials science forum, 2014)
The collection shows the importance of neutron and synchrotron radiation in the evaluation of mechanical stresses. It gathers the current knowledge from those concerned with the mechanical stress evaluation of materials and components using neutron and synchrotron radiation. It also gives an interesting "snap-shot" of progress in the field. The wide array contributions focus on the following key topics: Stress evaluation using neutrons, synchrotron radiation and X-rays; Development of measurement methods and instrumentation; Material processing and residual stresses; The influence of residual stresses on the physical and mechanical properties of materials and components; Measurement and assessment of residual micro-stresses and intergranular stresses; Residual strains and stresses in complex materials (e.g. multi-phase and biomaterials); Industrial applications of residual stress analysis using neutrons, synchrotron radiation and X-rays; and Complementary techniques for residual stress measurements. Keyword: Stress evaluation using neutrons, synchrotron radiation and X-rays; Development of measurement methods and instrumentation; Material processing and residual stresses; The influence of residual stresses on the physical and mechanical properties of materials and components; Measurement and assessment of residual micro-stresses and intergranular stresses; Residual strains and stresses in complex materials (e.g. multi-phase and biomaterials); Industrial applications of residual stress analysis using neutrons, synchrotron radiation and X-rays The 43 papers discuss such topics as a validated numerical model for predicting residual stress in an eight-pass-welded stainless steel plate, studying the asymmetric rolling of titanium by the finite element method with an implemented crystalline model, investigating the strain and texture of polyphase gneisses with neutron-time-of-flight diffraction, characterizing new generations of implants at the interface with bone by synchrotron radiation, and measuring residual stresses in aluminothermic rail welds using neutron diffraction techniques. -- Assessment and testing-- Materials science-- Mechanical engineering